THE EFFECT OF PROFITABILITY, LEVERAGE, AND FIRM SIZE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN TRANSPORTATION AND LOGISTICS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2020-2024 PERIOD - Yesa Meliani; Rawi Rawi (Majapahit Journal of Islamic Finance and Management, 2026)
This study analyzes the effect of profitability, leverage, and firm size on Corporate Social Responsibility (CSR) disclosure in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The urgency of the study is based on the increase in greenhouse gas emissions in the sector, which requires special attention regarding sustainability reporting. Using a causal quantitative design, a sample of 18 companies (90 observations) was selected through a purposive sampling method. Data analysis utilized panel data regression. The results show that profitability and leverage have no significant effect on CSR disclosure. However, firm size has a significant positive effect. The Adjusted R-Squared value indicates that the independent variables can explain the CSR disclosure variance by 51.16%. These findings support the integration of legitimacy and stakeholder theories, where large-scale companies with high public visibility proactively use CSR reporting as a strategic instrument to respond to global stakeholders' pressures. Therefore, management is advised to continuously strengthen the transparency of social responsibility information, while regulators should formulate stricter guidelines for smaller entities.